School Violence Against Mapuche Indigenous Students In Chilean Secondary Schools. (25th July 2015) - Becerra, Sandra; Mansilla, Juan; Merino, Maria Eugenia; Rivera, Pablo
Abstract: School violence on ethnic or racial grounds is a relevant problem in culturally diverse educational contexts. The purpose of this study was to identify the types of ethnic violence experienced by indigenous Mapuche adolescents at school. The study is qualitative-descriptive in design. The subjects of the study were 60 students from the Araucania Region of Chile. Results show three main modes of perceived school violence on ethnic grounds. All the modes of school violence found displayed underlying derrogatory attributions of ethnic prejudice towards indigenous students, and constituted a perpetual cycle of mistreatment towards ethnic groups in the school.